Considerations about the effectiveness and cost effectiveness of therapies in the treatment of hyperphosphataemia - Thomas Plagemann; Anne Prenzler; Thomas Mittendorf (Health Economics Review, 2011)
Because of an elevated serum phosphate level, patients who suffer from chronic kidney failure frequently tend tohave cardiovascular calcification and are therefore exposed to a higher probability of a fatal event. Phosphate binders are able to reduce these negative effects. Currently, there are primarily two groups of phosphate binders (calcium-containing and calcium-free phosphate binders) which are considered to be almost equally effective in terms of binding of free phosphate. There are, however, a few disadvantages of the two groups. While the calcium-containing binders are associated with an increased risk of hypercalcaemia, which is dose dependent, calcium-free binders have been criticized as being too expensive. As the expenditure for patients suffering from chronic kidney failure increases from year to year, as a result of increasing prevalence, there is a growing need for an alternative to existing phosphate binders. The study presented here therefore summarizes available information for the novel combination preparation OsvaRen® (calcium acetate/magnesium carbonate) as an alternative therapy to the calcium-free phosphate binder Renagel® (sevelamer-hydrochloride) and to calcium-containing preparations. The results of this systematic review showed that OsvaRen® is at least equally effective in the regulation of serum phosphate level as Renagel®. In particular, OsvaRen® shows no clinically relevant difference in terms of the control of the serum calcium levels compared to Renagel® and thereby does not increase the risk of a hypercalcaemia, in contrast to pure calcium-based phosphate binders. On the other hand, Renagel® therapy is much more frequently associated with gastrointestinal side-effects, a tendency to result in higher tablet burden for patients and high medication costs. The CALMAG study showed that OsvaRen® was at least as effective and safe in terms of controlling serum phosphate and serum calcium levels as Renagel® while, at the same time, resulting in about 80% lower costs. In addition, OsvaRen® offers a lower risk of hypercalcaemia and associated subsequent costs and is thereby also superior to pure calcium-containing phosphate binders. Because of the effectiveness and tolerability of calcium acetate/magnesium carbonate, OsvaRen® offers a clinically suitable and, at the same time, cost-effective therapeutic option in the therapy of hyperphosphataemia.
Keywords: 330